Semi-artificial Induced spawning of the Silver Pomfret Pampus argenteus (Euphrasen 1788) in KHour Abdullah, Basra, IRAQ - Al-Mukhtar, Mustafa A.; Mustafa, F. Mustafa A K; Mutlak, Falah M.; Hassan, Audi M.; Hameed, Tariq H.; Ramadan, Ismail A. (Iraqi Journal of Aquaculture, 2022)
Pampus argenteus (Euphrasen, 1788) is one of the most commercially important fish in the North Gulf region, Iraq in particular. It's stocks were critically endangered. The study showed the semi-artificial spawning. The mature brooders were collected from the region corresponding to the Khor Al-Zubair. The semiartificial spawning was done by mixing the sperm and ova of the live fish. It was found that fishes collected in the afternoon were most suitable for semi-artificial spawning. This research was able to diagnose the place and time of spawning fish, and time getting semen and its preservation, time to get mature eggs, access to the mechanism of action and necessary equipment. In addition to planning for subsequent phases of fertilized eggs rearing, hatching and larval rearing.